2000
DOI: 10.1007/s100380070019
|View full text |Cite
|
Sign up to set email alerts
|

Association of essential hypertension in elderly Japanese with I/D polymorphism of the angiotensin-converting enzyme (ACE) gene

Abstract: Recent evidence suggests that an insertion/deletion (I/D) polymorphism of the gene encoding angiotensinconverting enzyme (ACE) is associated with myocardial infarction and related cardiovascular diseases. We investigated a possible association of the ACE polymorphism with essential hypertension in a total of 263 cases/controls from among the elderly (age, over 70 years) and middle-aged (age between 30 and 60 years) Japanese population. The frequency of the I/I homozygote was significantly higher in hypertensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Moreover, in our analysis of elderly hypertensives, we found no significant association between ACE I/D polymorphism and hypertension. However, other reports have shown that genetic variation at the ACE locus may be associated with some determinants for blood pressure in the elderly (5,11). These discrepant results may suggest that there is actually very little or no association between the ACE I/D genotypes and hy-…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Moreover, in our analysis of elderly hypertensives, we found no significant association between ACE I/D polymorphism and hypertension. However, other reports have shown that genetic variation at the ACE locus may be associated with some determinants for blood pressure in the elderly (5,11). These discrepant results may suggest that there is actually very little or no association between the ACE I/D genotypes and hy-…”
Section: Discussionmentioning
confidence: 91%
“…There were no differences or changes in blood pressure in relation to ACE I/D polymorphism in our study. However, recent reports have suggested that an ACE I/D polymorphism is associated with age-related essential hypertension (2,5,9,11). Moreover, some studies have recently suggested that there is a sex-specific association between this gene and hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic predisposition to carotid atherosclerosis has been studied with respect to several candidate genes. Because the renin-angiotensin system (RAS) plays a pivotal role in the regulation of blood pressure, as well as in cardiovascular remodeling, the genes encoding the components of RAS have been the focus of much research (Hegele et al 1998;Nakauchi et al 1996;Takami et al 1998;Yoshida et al 2000). An insertion/deletion (I/D) polymorphism of the gene encoding angiotensin-converting enzyme (ACE) was shown to have a possible association with intima-media thickness (IMT) in several studies (Castellano et al 1995;Kogawa et al 1997;Pujia et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…24 In contrast, the D allele of the ACE I/D polymorphism has been associated with atherosclerosis. 7 Retinal arteriolar narrowing, which reflects intimal thickening, medial hyperplasia and hyalinization and sclerosis of retinal arterioles has also been associated with atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%